A multiscale investigation elucidating the structural complexities and electrochemical properties of layered–layered composite cathode materials synthesized at low temperatures. Issue 10 (4th February 2020) - Kaewmala, Songyoot; Wiriya, Narinthorn; Chantrasuwan, Patcharapohn; Yordsri, Visittapong; Limphirat, Wanwisa; Muhammad, Shoaib; Yoon, Won-Sub; Nash, Jeffrey; Srilomsak, Sutham; Limthongkul, Pimpa; Meethong, Nonglak
Abstract : 0.5Li2 MnO3 ·0.5LiCoO2 composite cathodes prepared using various heating and cooling rates under 600 °C reveal different microstructural characteristics that significantly impact their structural stability and electrochemical properties. Abstract : Layered–layered composite ( x Li2 MnO3 ·(1 − x ) LiMO2, M = Mn, Ni, Co, and Fe) cathode materials have attracted much attention as cathodes for high energy density lithium ion batteries. However, these materials are structurally unstable resulting from complicated phase transformation mechanisms during cycling. Additionally, the complex structural characteristics and structural stability of these materials largely depend on their preparation methods. Studying the correlation between multiscale structural properties and preparation methods is important in the development of layered–layered composite cathode materials. In this work, 0.5Li2 MnO3 ·0.5LiCoO2 composite materials were prepared with different heating and cooling rates with a maximum temperature of 600 °C. The structural properties of the 0.5Li2 MnO3 ·0.5LiMO2 composite materials were investigated using combined in situ X-ray absorption spectroscopy (XAS), in situ X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), and high resolution transmission electron microscopy (HRTEM) techniques. Heating and cooling rates have no significant effect on either the crystal or local atomic structures of the prepared samples. However, the microstructure was critically important for its impact on electrochemical properties.